ANALISA VARIASI SKEMA PUTUSAN PENGADILAN PAJAK ATAS TRANSAKSI KEPADA PIHAK YANG MEMILIKI HUBUNGAN ISTIMEWA - Henry Wijaya; Raden Arja Sadjiarto (Tax & Accounting Review, 2014)
This study aimed to understand the schemes of tax court decision on transactions between realted parties or affiliated transactions that occurred in Indonesia. All tax court decisions in this study were all tangible goods which were adjudged between 2013 to 2014.The results of this study showed that the main dispute of 5 cases from 7 cases, or approximately 71,4% are the comparables,in the analysis of the arm’s length principle, either in the level of transaction or to the level parties that become camparables. The other main disputes were the value of makr up or gross profit margin, the rules or guidelines for transfer pricing, the related parties, the methods of analyzing used,and the decision of tax objection letters. From those 7 cases, 5 of them can be grouped as tax avoidance and 2 of them as tax evasion.